PENGARUH KONSUMSI ENERGI DAN PENGELUARAN PERTAHANAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Roza Revika; Yeniwati Yeniwati (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to analyze the effect of energy consumption and defense expenditure on economic growth partially in theshort and long term in Indonesia. This study uses secondary data with descriptive analysis using Time Series data from 1988 to 2017. The analytical method used is Auto Regression Distributed Lag (ARDL). The results of this study indicate that energy consumption in the long run has a negative and significant effect on economic growth in Indonesia. Energy consumption in the short term has a negative and not significant effect on economic growth in Indonesia. Defense spending has a positive and significant effect on economic growth in Indonesia in the long term and in the short term. It can be concluded that in the long run energy consumption and defense expenditure significantly influence economic growth in Indonesia.